The role of scientific research in supporting private sector companies to achieve sustainable development: Field study in private sector companies operating in Benghazi - Shaitir, Fathya Jebril (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to clarify the impact of using scientific research and its components in managing the operations of private sector companies in achieving sustainable development in Libya. It also explores how scientific research can contribute to supporting private sector companies in achieving sustainable development. To answer the study’s questions and achieve its objectives, a quantitative methodology was adopted, utilizing a questionnaire to collect data from a population of 60 private industrial sector companies. A sample of 52 companies was selected from this population, with 47 companies agreeing to receive the questionnaire. Out of these, 40 questionnaires were subjected to statistical analysis, as the remaining 7 were deemed invalid. To analyze the data and test the hypotheses, the Statistical Package for the Social Sciences (SPSS) was used. Descriptive and analytical statistical tests were conducted. The study reached several conclusions, the most important of which was the acceptance of all sub-hypotheses at a significance level of 0.05, using a one-sample t-test. This implies the acceptance of the main hypothesis of the study, which states that "the use of scientific research and its components in managing private sector companies’ operations affects the achievement of sustainable development in Libya." This was confirmed through linear regression analysis, which showed the impact of the independent variable "utilizing scientific research to solve problems in implementing the business plans of Libyan private sector companies" on the dependent variable "the role of scientific research in achieving sustainable development." This fulfills the objective of the study.